2021
DOI: 10.21608/ijma.2021.62186.1260
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Biocides Resistance Genes among Clinical Isolates of Both Methicillin-Resistant and Methicillin-Sensitive Strains of Staphylococcus Aureus

Abstract: BACKGROUND: Biocides compounds are widely used in infection control programs, including hand washing and skin decolonization before invasive procedures. However, its overuse leads to the emergence of Staphylococcus aureus with decreased biocides susceptibility, which became a problem in hospitals in different parts of the world. AIM OF THE WORK:The present work aims to study the susceptibility of methicillin-resistant isolates of staphylococci aureus, obtained from different clinical samples to commonly used b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Furthermore, in vitro results showed that sublethal concentrations of hydrogen peroxide or biocides based on hydrogen peroxide were responsible for the transfer of prophage Φ13 from human S. aureus donor strain to livestock-associated MRSA CC398 61599 recipient strain. Clinically relevant isolates (MRSA and MSSA) can encode biocide resistance genes such as qac A/B and qac C [ 100 ]. An illustration of biocide resistance was described in S. aureus strains isolated from clinical samples from Egypt and showed that the presence of qacA/B genes caused increased MICs of sodium hypochlorite, phenol, and Savlon (chlorhexidine digluconate 0.3% and cetrimide 3%).…”
Section: The Effect Of Biocides Against Foodborne Pathogenic Bacteriamentioning
confidence: 99%
“…Furthermore, in vitro results showed that sublethal concentrations of hydrogen peroxide or biocides based on hydrogen peroxide were responsible for the transfer of prophage Φ13 from human S. aureus donor strain to livestock-associated MRSA CC398 61599 recipient strain. Clinically relevant isolates (MRSA and MSSA) can encode biocide resistance genes such as qac A/B and qac C [ 100 ]. An illustration of biocide resistance was described in S. aureus strains isolated from clinical samples from Egypt and showed that the presence of qacA/B genes caused increased MICs of sodium hypochlorite, phenol, and Savlon (chlorhexidine digluconate 0.3% and cetrimide 3%).…”
Section: The Effect Of Biocides Against Foodborne Pathogenic Bacteriamentioning
confidence: 99%